Chemometrics in forensic science - Kumar, Raj; Sharma, Vishal (TrAC, Trends in analytical chemistry (Regular ed.), 2018)
This review represents a detailed discussion of the multivariate methods used in the examination of forensic exhibits; their advantages, disadvantages, and efficiency are compared. The last decade has seen the application of the chemometric methods combined with analytical techniques for characterization and discrimination of samples, which leads to the informative and representative examinations of the samples. Many research articles with reference to the use of chemometrics in forensic science have been published. This review has been divided into various sections which include chemometrics, its history, multivariate methods, and the application of chemometrics in various disciplines of forensic science. It is suggested that these new techniques and mathematical/statistical methods should be utilized in forensic science casework to get statistical confidence in the results. •Chemometrics: Its history, types and application in various disciplines of forensic science.•Combined approach of analytical and multivariate methods; their advantages and disadvantages.•Chemometric methods are expedient due to their ease of interpreting results, reliability, and speed.•Advanced modeling methods such as SIMCA and SVM are gaining popularity.